Enhanced rehabilitation guidance after arthroscopic capsulolabral repair of the shoulder: a randomized controlled trial - Multanen, Juhani; Kiuru, Pauli; Piitulainen, Kirsi; Ylinen, Jari; Paloneva, Juha; Häkkinen, Arja (Clinical rehabilitation, 2020)
To compare the effects of a 12-month home-based exercise program to usual care in patients after arthroscopic capsulolabral repair of the shoulder. Randomized controlled trial. Outpatient physical and rehabilitation medicine clinic. Forty-five patients (mean age: 35 years; standard deviation (SD): 10 years) who underwent arthroscopic capsulolabral repair due to labral lesion were randomized into an exercise group (EG) or a control group (CG). The EG received a 12-month home-based additional exercise program with four physiotherapy follow-up visits, while the CG received standard postoperative exercise instructions. Self-reported shoulder disability was assessed with the American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form (ASES) and quality of life with the Short-Form (SF)-36 Health Survey. The function of the operated shoulder was evaluated with strength and range of motion measurements. No between-group differences were observed in any of the outcomes at the follow-up. Mean ASES score improved by 16 (95% confidence interval (CI): 10-23) points from the baseline 78 (SD: 17) in the EG and 13 (95% CI: 7-19) points from the baseline 79 (SD: 17) in the CG. Both groups achieved a significant improvement in the dimensions of Physical Functioning, Role-Physical, and Bodily Pain of the SF-36 and in every aspect of strength and range of motion measures. In EG, exercise adherence was moderate (52%) during the first six months and poor (22%) during the last six months. Home-based additional exercises with four outpatient follow-up visits did not improve outcome after arthroscopic capsular repair of the shoulder.